Flow cytometry study of DNA transformation dynamics in ВНК-21/SUSP/ARRIAH cell culture during rabies virus reproduction - M. N. Guseva; M. I. Doronin; M. A. Shevchenko; D. V. Mikhalishin; A. V. Borisov; Yu. S. El’kina; T. V. Okovytaya; V. М. Zakharov; V. V. Mikhalishin (Ветеринария сегодня)
The study examines the DNA transformation dynamics of ВНК-21/SUSP/ARRIAH subline cells during rabies virus reproduction. Cells infected with the virus and control intact cells were cultivated under similar conditions. The identification of dependence of the virus infectivity on reproduction time revealed that the virus infectivity titre increased from (3.2 ± 0.2) lg CCID50/cm3 at the time of inoculation to (7.63 ± 0.3) lg CCID50/cm3 after 48 hours of reproduction, with the most intensive increase having been observed within the first 24 hours. The cell concentration changed from 0.5 to 1.9 million/cm3, i.e. increased by a factor of 3.8. After 24 hours, the cell growth rate slowed down. Findings from the examination of cell cycle phases during rabies virus reproduction in the host cell allowed for the estimation of duration and predominance of G1, S, G2 + M phases at different stages of cultivation. The dynamics of changes in the apoptotic cell population in the control and test samples was similar within 36 hours of cultivation. After the said period, the proportion of apoptotic infected cells was 28–42% higher than that of apoptotic control cells. After 9 hours, the proportion of cells undergoing G1 phase increased by 11.7% in the test samples, whereas it decreased by 16.6% in the control samples. Subsequently, the number of G1 phase cells in the control and test samples changed in the same way: a 40% decrease was observed after 15–18 hours, it was followed by a 45–46% growth jump, then again a 39–40% decrease and an increase were observed. After 33 hours of reproduction and till the end of cultivation, the proportion of infected cells undergoing G1 phase was significantly higher (by 12–21%) as compared with control cells. The percentage of S phase cells in the test and control samples was the same during the first day of the virus reproduction, with sharp jump-like 3.4- and 2.4-fold increases having been observed after 15 and 24 hours, respectively. After 24 hours, the infected and control cells began to demonstrate differences, which gradually increased from 8 to 137% by the end of reproduction. After 30 hours of reproduction, the proportion of test sample cells undergoing G2 + M phase began to decrease by 17–28% as compared with the control cells. The cell switch-over to the synthesis of complete rabies virus particles occurred after 24 hours of reproduction. This is indicated by changes in the host cell cycle phases, as well as by the slowing down of ВНК-21/SUSP/ARRIAH cell population growth.